Club Rugby, the University Student Collegiate Experience, and Perceived Gains. Issue 1 (April 2019) - Martin, Eric; Unfried, Alana; Beckham, George
To examine the relationship between club rugby participation, collegiate experiences, and perceived gains, 37 rugby players and 33 nonathlete students completed the Student-Athlete Experiences Inventory–Revised, Student-Athlete Gains Inventory, and Perceived Stress Scale at the start of a Spring semester. Linear regressions were used to determine the relationship between rugby participation, stress, participation in experiences, and perceived gains of students. The two gains modeled were practical and liberal arts gains. Practical arts gains were predicted positively by the experiences of active campus involvement and social interaction, while rugby was a negative predictor, adjusted R 2 = .280, F (3, 65) = 10.90, p < .0001. Liberal arts gains were predicted by social interaction, academic pursuits, and active involvement, adjusted R 2 = .22, F (4, 64) = 6.06, p = .0005. This study confirms how experiences predict different perceived gains. Club rugby players should be encouraged to take advantage of support services on campus to prepare them for their careers.